2016
DOI: 10.3389/fneur.2016.00113
|View full text |Cite
|
Sign up to set email alerts
|

Aging Increases Compensatory Saccade Amplitude in the Video Head Impulse Test

Abstract: ObjectiveRotational vestibular function declines with age resulting in saccades as a compensatory mechanism to improve impaired gaze stability. Small reductions in rotational vestibulo-ocular reflex (VOR) gain that would be considered clinically normal have been associated with compensatory saccades. We evaluated whether compensatory saccade characteristics varied as a function of age, independent of semicircular canal function as quantified by VOR gain.MethodsHorizontal VOR gain was measured in 243 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 41 publications
3
55
5
6
Order By: Relevance
“…They reportd that the presence of covert saccades despite normal VOR gain is a correction of eye drifts to the target position and it has been suggested that the presence of refixation saccades with normal VOR gain is part of the process of aging of the vestibular system. 23 Yollu et al, 24 reported significantly higher covert saccades in migraine patients compared to healthy controls, and suggested that these saccades were associated with the connection between the trigeminal nerve and the vestibular nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…They reportd that the presence of covert saccades despite normal VOR gain is a correction of eye drifts to the target position and it has been suggested that the presence of refixation saccades with normal VOR gain is part of the process of aging of the vestibular system. 23 Yollu et al, 24 reported significantly higher covert saccades in migraine patients compared to healthy controls, and suggested that these saccades were associated with the connection between the trigeminal nerve and the vestibular nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Saccade amplitude usually correlates with gain deficit in peripheral vestibulopathy; 3,43 however, one particular pattern, "normal gain with catch-up saccade," is a well recognized exception, which is associated with increasing age, thought to be because of the slight gain reduction, gaze positional error correction independent of VOR, and inability to suppress saccades to novel targets. 47,48…”
Section: Performing Vhitmentioning
confidence: 99%
“…Kompensatorische Sakkaden zeigten keine Altersabhängigkeit. Auch andere Arbeitsgruppen konnten eine Reduktion des Gainwertes im höheren Lebensalter ( > 70) nachweisen [146][147][148][149]. Anson et al wiesen auf den Zusammenhang einer Gainreduktion mit einer Zunahme der Amplitude von Korrektursakkaden im Alter hin.…”
Section: Bewertung Der Ergebnisseunclassified
“…Anson et al wiesen auf den Zusammenhang einer Gainreduktion mit einer Zunahme der Amplitude von Korrektursakkaden im Alter hin. Dies wird mit einer Beeinträchtigung hochfrequenter, irregulärer vestibulärer Typ-1-Fasern durch "Altersprozesse" erklärt [146,147]. Die Interpretation im höheren Lebensalter (ca.…”
Section: Bewertung Der Ergebnisseunclassified
See 1 more Smart Citation